2014
DOI: 10.1177/1049732314538550
|View full text |Cite
|
Sign up to set email alerts
|

Renegotiating Identities

Abstract: Along with major changes in mood, people living with bipolar disorder (BD) often experience recurrent hospital admissions, feelings of failure and hopelessness, social stigma, underemployment, and a loss of independence. In this study we explored the experiences of loss, coping, and recovery in a community sample of women living with BD. Ten women each participated in a semistructured interview. We used the constant comparative method to analyze the data. We identified three themes from the data: identity boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Similar themes of inconsistency have emerged in adult samples as well (Jonsson, Wijk, Skarsater, & Danielson, 2008). One study using a theoretical sampling method found that many with bipolar disorder highlighted a theme of inconsistency, and its negative effects on relationship continuity (Fernandez, Breen, & Simpson, 2014). This same study found that people described feeling at once out of control and over-scrutinized by others who were concerned that they may lose control.…”
Section: Great Expectations and Self-worth Based On Achievement: Potential Clinical Implicationsmentioning
confidence: 75%
See 1 more Smart Citation
“…Similar themes of inconsistency have emerged in adult samples as well (Jonsson, Wijk, Skarsater, & Danielson, 2008). One study using a theoretical sampling method found that many with bipolar disorder highlighted a theme of inconsistency, and its negative effects on relationship continuity (Fernandez, Breen, & Simpson, 2014). This same study found that people described feeling at once out of control and over-scrutinized by others who were concerned that they may lose control.…”
Section: Great Expectations and Self-worth Based On Achievement: Potential Clinical Implicationsmentioning
confidence: 75%
“…Persons with bipolar disorder who adopt a "patient identity" tend to adhere to medications, but also report feelings of powerlessness (Fernandez et al, 2014). Participants described feelings of failure bred from a perceived discontinuity in mood, confidence, or values.…”
Section: Great Expectations and Self-worth Based On Achievement: Potential Clinical Implicationsmentioning
confidence: 99%
“…The notion of becoming the director of your own life resembles themes in earlier research such as fostering self-empowerment (Young & Ensing, 1999), independence and autonomy (Michalak et al, 2006), taking responsibility (Todd, Jones, & Lobban, 2012), or claiming control (Chapman, 2002;Fernandez et al, 2014). Individuals reported actively defining their own route to recovery and seeking guidance when necessary.…”
Section: Findings In the Context Of Current Literaturementioning
confidence: 91%
“…It also enabled those taking medication or involved in services to not be excluded. The criteria of 4 years or more since a previous episode aimed to capture people who have achieved a longer recovery period than those previously studied (e.g., Fernandez, Breen, & Simpson, 2014;Veseth, Binder, Borg, & Davidson, 2012). In addition, the inclusion of any previous BD diagnosis extended the viewpoints captured beyond a focus on bipolar I (Mansell et al, 2010).…”
Section: Study Aimsmentioning
confidence: 99%
“…This overcoming, or response to loss, is often viewed as grief that ‘permeates all facets of our lives’ ( Goldsworthy, 2005 , p. 167). Most of what we understand about loss is based on death losses (e.g., bereavement) rather than non-death losses (e.g., loss of employment) ( Fernandez et al, 2014 ; Goldsworthy, 2005 ; Harris, 2019 ). Dominant approaches to understanding people’s loss and grief tend towards more individualistic, psychological and clinical/medical lenses ( Goldsworthy, 2005 ).…”
mentioning
confidence: 99%